2008
DOI: 10.1016/j.molcel.2007.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Dcn1 Functions as a Scaffold-Type E3 Ligase for Cullin Neddylation

Abstract: Cullin-based E3 ubiquitin ligases are activated through modification of the cullin subunit with the ubiquitin-like protein Nedd8. Dcn1 regulates cullin neddylation and thus ubiquitin ligase activity. Here we describe the 1.9 A X-ray crystal structure of yeast Dcn1 encompassing an N-terminal ubiquitin-binding (UBA) domain and a C-terminal domain of unique architecture, which we termed PONY domain. A conserved surface on Dcn1 is required for direct binding to cullins and for neddylation. The reciprocal binding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
191
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(202 citation statements)
references
References 51 publications
11
191
0
Order By: Relevance
“…Thus, the Ubc12 sites for binding to Smurf1 appear to largely overlap with that for the E1. The previously identified Nedd8 ligation-promoting factor Dcn1 binds Ubc12 in the same pattern 23 . In addition, deletion analysis indicated that the Smurf1 HECT N-lobe small subdomain mediated the interaction with Ubc12 (Fig.…”
Section: Smurf1 Interacts Withmentioning
confidence: 66%
See 2 more Smart Citations
“…Thus, the Ubc12 sites for binding to Smurf1 appear to largely overlap with that for the E1. The previously identified Nedd8 ligation-promoting factor Dcn1 binds Ubc12 in the same pattern 23 . In addition, deletion analysis indicated that the Smurf1 HECT N-lobe small subdomain mediated the interaction with Ubc12 (Fig.…”
Section: Smurf1 Interacts Withmentioning
confidence: 66%
“…Smurf1 can be neddylated by itself or by other Nedd8 ligase(s). Among the currently known Nedd8 ligases (that is, Dcn1, Roc1/ Rbx1, MDM2, IAPs and c-Cbl) 6,13,23,25,[39][40][41][42] , only MDM2 was demonstrated to interact with Smurf1 (ref. 43).…”
Section: Smurf1 Interacts Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there was a putative Rad53 binding site. Recently, researchers uncovered a novel MEC1-RAD53-DCN1-dependent signaling pathway that prevented deleterious DSB-specific telomerase additions at DNA breaks, thus preserving genomic integrity (Makovets et al, 2009;Kurz et al, 2008). Taken together, these findings suggested that the DCUN1D5 might play a role in DNA damage response to genotoxic stress and probably subsequent DNA repair.…”
Section: Discussionmentioning
confidence: 97%
“…Early studies demonstrated that cullin neddylation is required for efficient ubiquitylation and/or turnover of CRL substrates in vivo, which has been borne out through the development of MLN4924, a small-molecule inhibitor of NAE [14,[48][49][50]. Inhibition of CRL activity by MLN4924 results in accumulation of a host of CRL targets [14,43,51,52].Structural and biochemical studies revealed a complex mechanism underlying cullin neddylation that involves dual E3 activity and co-translational modification of neddylation E2s to strongly activate the transfer of NEDD8 to the cullin [39,44,53,54]. Early studies indicated that UBC12 can neddylate CUL1 in vitro in a manner that requires RBX1 [55][56][57] For simplicity, therefore, we refer to Cdc53 as yeast CUL1 throughout.…”
mentioning
confidence: 99%